Investigation of the flocculation and sedimentation of TiO2 nanoparticles in different alcoholic environments through turbidity measurements - Abavi Torghabeh, Naghmeh; Raissi, Babak; Riahifar, Reza; Sahbayaghmaee, Maziar; Minaei Bidgoli, Zahra (Journal of Composites and Compounds, 2021)
Turbidimeters are low-cost devices, which are widely used for suspended sediment monitoring (SSM). The specific turbidity is typically relative to 1/d (d is the diameter of particles) regarding the suspensions with mono-sized sphere-shaped particles. As the production of the dispersed suspension of TiO2-NPs is vital for their photocatalysis applications, turbidity provides a test to measure the dispersion of TiO2-NPs. In the present paper, the performance of a self-manufactured turbidimeter device has been investigated using the suspensions of TiO2-NPs in different alcoholic media. The results showed that over time, the intensity of light passing through the upper part of the test tube containing TiO2-NPs suspension increased, suggesting the settlement of TiO2 nanoparticles. In the middle part of the test tube; however, an almost stable trend was observed, which was more evident in the case of isopropanol with higher viscosity. The results also illustrated that there was no relation between the concentration of suspension and the value of transmitted light for concentration below 0.08 g/l; however, for concentrations above that, the intensity of transmitted light decreased with the increase of suspension concentration.